2013
DOI: 10.1177/0145721713492570
|View full text |Cite
|
Sign up to set email alerts
|

Who Can Provide Diabetes Self-Management Support in Primary Care?

Abstract: These findings reaffirm the critical role of educators but suggest that others may serve as DSMS supporters. Results suggest that DSME delivered in primary care is effective and multiple DSMS agents are reasonable. As patient-centered self-management approaches are being explored in primary care, delivery of DSME and DSMS becomes paramount.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 15 publications
3
62
0
Order By: Relevance
“…Studies have shown that implementing DSME programs that directly connect with primary care and rely on technology is effective in improving clinical, psychosocial, and behavioral outcomes (16,(71)(72)(73)(74). Patients receiving care in these practice settings report more confidence in provider communication and satisfaction with direct access to an educator for information and ongoing support (16).…”
Section: Overcoming Barriers That Limit Access and Receipt Of Dsme/smentioning
confidence: 99%
“…Studies have shown that implementing DSME programs that directly connect with primary care and rely on technology is effective in improving clinical, psychosocial, and behavioral outcomes (16,(71)(72)(73)(74). Patients receiving care in these practice settings report more confidence in provider communication and satisfaction with direct access to an educator for information and ongoing support (16).…”
Section: Overcoming Barriers That Limit Access and Receipt Of Dsme/smentioning
confidence: 99%
“…21,26,27,30,37 In contrast, the pooled effect size from the 7 studies with predominantly white, non-Hispanic participants showed no improvement in HbA 1c level with peer support interventions, with an SMD of -0.004 (95% CI, -0.153 to 0.144; P = .95; I 2 = 59.41%). 22,25,29,[31][32][33][34] The pooled effect in the subgroup of 3 studies with predominantly African American participants showed a similar effect size to that seen in the Hispanic subgroup but was not statistically significant, with an SMD of 0.25 (95% CI, -0.064 to 0.571; P = .11; I 2 = 58.60%). 23,24,28 The differences in effect sizes between ethnicity subgroups were statistically significant, with a between-group P value of .03.…”
Section: Subgroup Analyses Studies With Ethnic or Racial Predominancementioning
confidence: 72%
“…20 Ultimately, 14 articles with RCT designs and 3 cluster RCTs were eligible for inclusion in the meta-analysis, for a total of 4,715 participants. Of the 17 trials, 10 were done in the United States, [21][22][23][24][25][26][27][28][29][30] …”
mentioning
confidence: 99%
“…Patients with T2DM typically get most of their diabetes care in short visits from family physicians that may or may not have additional multi-disciplinary support. In addition, OHIP covers services provided by DEPs, which are multi-disciplinary, non-physician led programs designed to deliver self-management education of diabetes and self-management support [18]. The three recruitment sites included 1) a DEP located in an urban area in a large city centre (>2 million people 2) a DEP located in a mid-size city in a remote area of the province (<150,000 people) and 3) a DEP located in a semi-urban area surrounding a large city centre (<600,000 people).…”
Section: Settingsmentioning
confidence: 99%